Molecular imaging biomarkers in familial frontotemporal lobar degeneration: Progress and prospects - Wang, Ruihan; Gao, Hui; Xie, Hongsheng; Jia, Zhiyun; Chen, Qin (Frontiers in Neurology, 2022)
Familial Frontotemporal lobar degeneration (FTLD) is a pathologically heterogeneous group of neurodegenerative diseases with diverse genotypes and clinical phenotypes. Three major mutations reported in patients with familial FTLD include GRN, MAPT, and the C9orf72 repeat expansion, which could cause neurodegenerative pathological changes years before symptom onset. Non-invasive quantitative molecular imaging with Positron emission tomography (PET) or single-photon emission computed tomography (SPECT) allows for selectively visualization of the molecular targets in vivo to investigate the brain metabolism, perfusion, neuroinflammation and pathophysiological changes. There was increasing evidence that several molecular imaging biomarkers tend to serve as biomarkers to reveal the early brain abnormalities in familial FTLD. Tau-PET with 18F-flortaucipir and 11C-PBB3, demonstrated the elevated tau position in patients with FTLD and also showed the ability to different patterns among the different subtypes of the mutations in familiar FTLD. Furthermore, Dopamine transporter imaging with the 11C-dopa and 11C-CFT in PET and the 123I-FP-CIT in SPECT, revealed the loss of dopaminergic neurons in the asymptomatic and symptomatic patients of familial FTLD. In addition, PET imaging with the 11C-MP4A has demonstrated reduced acetylcholinesterase (AChE) activity in patients with FTLD, while PET with the 11C-DAA1106 and 11C-PK11195 revealed increased level of microglial activation associated with neuroinflammation even before the onset of symptoms in familial FTLD. 18F-fluorodeoxyglucose (FDG) PET indicated hypometabolism in FTLD with different mutations preceded the atrophy on MRI. Identifying molecular imaging biomarkers for familial FTLD is important for the in vivo assessment of underlying pathophysiological changes with disease progression and future disease modifying therapy. We review the recent progress of molecular imaging in familial FTLD with focused on the possible implication of these techniques and their prospects in specific mutation types.